Technological entrepreneurship as a form of regional integration of business and education - V. N. Pishchulin; M. I. Shepelev (Вестник Северо-Кавказского федерального университета)
Introduction. Resisting the external constraints of the domestic economy and achieving high economic growth rates is impossible without focusing on innovative development and technological independence. In this regard, the development of technological entrepreneurship at the regional and state levels is an important task to achieve economic security of Russia. Goal. To show the prospects and obstacles for the development of technological entrepreneurship in Russia at the present stage. Materials and methods. The study is based on a comparative analysis of information on the state of technological entrepreneurship development in Russia as a whole and in individual regions, as well as a systematic analysis of areas of support for this type of business. Results and discussion. In the course of the work, the existing prerequisites and favorable conditions for the development of technological entrepreneurship in Russia are revealed, the need for regional integration of business and education to create centers for technological entrepreneurship is substantiated, and the main problems requiring a systematic solution are identified. Conclusion. Based on the results of the study, it can be concluded that technological entrepreneurship as the basis of the economic and technological independence of the state, if successfully implemented, can become a key driver of economic growth and the basis for the formation of the middle class.